Beneficial effects of pro-/antioxidant-based nutraceuticals in the skin rejuvenation techniques - De Luca, C.; Deeva, I.; Mikhal’chik, E.; Korkina, L.; Korkina, L. (Cellular and Molecular Biology, 2007)
Modern technologies of skin rejuvenation include many physical and chemical intervention tools - laser irradiation, oxygen and ozone therapy, chemical peels, plastic surgery operations - affecting by different mechanisms the sensitive physiological free radical / antioxidant balance in the skin. All these interventions induce from mild to severe tissue damage, providing beneficial biochemical stimuli for skin re-epithelization and rejuvenation. Paradoxically, free radical production in the course of tissue inflammation helps to combat free radical damage consequent to the ageing process. We have studied two animal models (experimental burn and trichloracetic peeling), reproducing on the Wistar rat the effects generated by the commonly practiced aesthetic medicine procedures of laser resurfacing and chemical peels, demonstrating that the severe oxidative stress induced both systemically and on skin can be modulated by the oral pre- and post treatment administration of specific nutraceutical formulations. Potent antioxidants (RRR-alpha-tocopherol, coenzyme Q10), enhancing antioxidant defences, coupled with mild pro-oxidants, enhancers of a specific immune defense (soy phospholipids, L-methionine), at the blood and the skin levels, proved in fact to be beneficial in vivo, on the rat, for skin healing, trophism and accelerated re-epithelization. Data obtained allow us to predict the possibility of innovative protocols for dermocosmetology, enabling successful lowering of the risk of permanent adverse effects, and prolonging the duration of the beneficial effects of dermocosmetologic procedures.